2023
DOI: 10.1302/2633-1462.45.bjo-2022-0140.r2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of morbidly obese patients undergoing total hip arthroplasty with the anterior-based muscle-sparing approach

Abstract: AimsObesity is associated with an increased risk of hip osteoarthritis, resulting in an increased number of total hip arthroplasties (THAs) performed annually. This study examines the peri- and postoperative outcomes of morbidly obese (MO) patients (BMI ≥ 40 kg/m2) compared to healthy weight (HW) patients (BMI 18.5 to < 25 kg/m2) who underwent a THA using the anterior-based muscle-sparing (ABMS) approach.MethodsThis retrospective cohort study observes peri- and postoperative outcomes of MO and HW patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We acknowledge the need to consider surgical risks as an important factor in preoperative evaluation. Reports in the literature provide more consistent results suggesting increased postoperative complications such as infection, readmission, and reoperation in obese patients [ 6 , 7 , 21 ]. These complications, however, are outside the scope of the current study as our objective was to compare pain, function, and satisfaction as a function of BMI classification.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We acknowledge the need to consider surgical risks as an important factor in preoperative evaluation. Reports in the literature provide more consistent results suggesting increased postoperative complications such as infection, readmission, and reoperation in obese patients [ 6 , 7 , 21 ]. These complications, however, are outside the scope of the current study as our objective was to compare pain, function, and satisfaction as a function of BMI classification.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, studies also report that patients with greater BMI have worse pain and function outcomes after THA. Shevenell et al [ 6 ] reported that patients with Class III obesity were found to have greater pain ( p = 0.041) and worse functional improvement (measured by HOOS JR, p = 0.002) 1 year after THA compared to healthy weight individuals. Our results demonstrate greater subjective functional improvements and pain reduction in higher obesity classes, which contrast with this previous report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been demonstrated that the beneficial effects of dietary fibers on the intestines may be diminished in obese children with pre-existing insulin resistance [ 18 ]. Furthermore, individuals classified as obese based on BMI classification face an increased risk of postoperative complications, as evident in hip arthroplasty [ 19 , 20 ]. In such cases, they are more susceptible to deep infections and femoral stem subsidence compared to normal-weight individuals.…”
Section: Introductionmentioning
confidence: 99%